Elevated ICAM5 as a promising predictor of poor prognosis in bladder cancer via EMT, immune microenvironment, and therapy resistance - Xiaolong Chen; Zhen Wang; Yangsheng Rong; Zhiqiang Zhu; Zheng Peng; Kunyuan Huang; Guanyun Deng; Di Liu; Qing Wang; Jianguo Zhu; Kun Chen; Kehua Jiang (PLoS ONE, 2026)
Background Bladder cancer, the most common malignancy of the urinary system, is associated with poor prognosis due to its metastatic potential, invasive behavior, and immune evasion. Intercellular adhesion molecule 5 (ICAM5), a member of the immunoglobulin superfamily, regulates cell adhesion and has been implicated in tumor progression. However, its biological function in bladder cancer remains unclear. Methods In this study, we analyzed data from The Cancer Genome Atlas (TCGA) and UCSC Xena databases to investigate ICAM5 expression, prognostic significance, genetic mutations, methylation, immune profiles, and regulatory functions in bladder cancer. Weighted Gene Coexpression Network Analysis (WGCNA) and Gene Set Cancer Analysis (GSCA) were employed to explore ICAM5-related pathways. Results Our findings demonstrated that ICAM5 expression was significantly upregulated in bladder cancer and associated with advanced disease features, including higher TNM stages, pathological grades, and aggressive molecular subtypes. Furthermore, ICAM5 influenced the immune microenvironment, regulated methylation, and modulated immune checkpoint expression, contributing to immunotherapy resistance. Mechanistically, ICAM5 promoted epithelial-mesenchymal transition (EMT), proliferation, and metastasis. Conclusions ICAM5 serves as a novel prognostic biomarker and potential therapeutic target in bladder cancer, orchestrating EMT progression, reshaping the immune microenvironment, and driving resistance to immunotherapy.